Size Inflation in Drawing From Mirror and Proportional Accuracy in Observational Drawing. (July 2020) - Lou, Leon
In three experiments, a bias to inflate in drawing the proportion of an image on a mirror over the mirror itself is demonstrated in a sample ( N  = 146) of undergraduate students taking introductory psychology classes. The inflation is not confined to the image of one's own head but is likely to occur in depictions of any object from a mirror with the mirror frame included. Having to include in the drawing background objects visible in the mirror is found to reduce the inflation. The inflation also diminishes with a smaller mirror and at a longer viewing distance. An account for the inflation in terms of a mechanism of size constancy contingent on selective attention is offered. The size of the inflation suggests a conflation of the perceived mirror image size with the size of the distal object it signals rather than a complete take-over by the latter. The reduction of the size inflation when participants are asked draw both a target and background objects is more likely a result of the selective attention to proportional relationships in the mirror scene, rather than a manifestation of an evenly scaled visual space under distributed visual spatial attention. The implications of the findings to improving proportional accuracy in observational drawing are discussed.